Maize grain price trends in food surplus and deficit areas of Mozambique under Covid-19 - Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Greffiths, Ikhothatseng Jacob; Fakudze, Bhekiwe (2020)
This bulletin presents an overview of maize price movements in Mozambique with the view of investigating whether there may be a relationship between the incidence of Covid-19 and maize price changes in local markets.